DMD Pluripotent Stem Cell Derived Cardiac Cells Recapitulate in vitro Human Cardiac Pathophysiology - Jelinkova, Sarka; Vilotic, Aleksandra; Pribyl, Jan; Aimond, Franck; Salykin, Anton; Acimovic, Ivana; Pesl, Martin; Caluori, Guido; Klimovic, Simon; Urban, Tomas; Dobrovolna, Hana; Soska, Vladimir; et al. (Frontiers in Bioengineering and Biotechnology, 2020)
Duchenne muscular dystrophy (DMD) is a severe genetic disorder characterized by the lack of functional dystrophin. DMD is associated with progressive dilated cardiomyopathy eventually leading to heart failure as the main cause of death in DMD patients. Although several molecular mechanisms leading to the DMD cardiomyocyte (DMD-CM) death were described, mostly in mouse model, no suitable human CM model was until recently available together with proper clarification of the CM phenotype and delay in cardiac symptoms manifestation. We obtained several independent dystrophin-deficient human pluripotent stem cell (hPSC) lines from DMD patients and CRISPR/Cas9-generated DMD gene mutation. We differentiated DMD hPSC into CMs creating a human DMD-CM disease model. We observed that mutation-carrying cells are less prone to differentiate into CMs. DMD CMs demonstrate an enhanced cell death rate in time. Furthermore, ion channel expression was altered in terms of potassium (Kir2.1 overexpression) and calcium handling (DHPR overexpression). DMD-CMs exhibited increased time of calcium transient rising compared to aged-matched control, suggesting mishandling of calcium release. We observed mechanical impairment (hypocontractility), bradycardia, increased heart rate variability, and blunted β-adrenergic response connected with remodeling of β-adrenergic receptors expression in DMD-CMs. Overall these results indicated that our DMD-CMs models are functionally affected by dystrophin-deficiency associated and recapitulate functional defects and cardiac wasting observed in the disease, offering an accurate tool to study human cardiomyopathy progression and test therapies in vitro.